PEMANFAATAN LIMBAH CANGKANG RAJUNGAN (PORTUNUS PELAGICUS) SEBAGAI PERISA MAKANAN ALAMI - Sri Hastuti; Syamsul Arifin; Darimiyya Hidayati (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
Crabshellwastefromcrabindustry cause enviromentalproblem. Someeffortswereneededtoovercometheproblem. Crabflavourwas a potentialproductwhich has createdusingcrabeggshell. Thisresearchaimedtochoosebestmethodeformakingcrabflavour and toknowtheinfluence of dextrinonitsquality. Theresearchwasdividedintotwostages (the process to make crabshell powder and crabshell flavour). Thepowderwascreatedbyusinghydrolysis and non-hydrolysis. Full randomizeddesignwaschoosenwheredextrin (1, 2, 3%) used as a single factor. According to the result, non-hydrolysis was choosen for making crab flavourer because it improved calcium content (26,82%) and aroma. Meanwhile, based on sensory evaluation, respondents clearly stated ”like” in aroma, taste, colours as well. Statistically, dextrin didn’t produce significant influence in moisture content, aroma, colour, and taste